SURAU AS EDUCATION INSTITUTIONS OF MUSLIM IN MINANGKABAU (STUDY THE ROLE SHEIKH BURHANUDDIN ULAKAN IN BUILDING EDUCATION SYSTEM OF SURAU IN MINANGKABAU 1100-1111 AH) - Harto, Jemmy (Tawazun: Jurnal Pendidikan Islam, 2018)
Surau is one of the classical Islamic educational institutions present a kind of pesantren in the history of Islamic education in Indonesia. Sheikh Burhanuddin Ulakan is the founder of surau as educational institutions in Minangkabau. Surau education system aims to explore the role of Sheikh Burhanuddin Ulakan in building the education system of surau, analyze the educational system, the objectives, programs, educational process and evaluation of education. The method used the qualitative research approach to field research and library research. The result of research obtained is the concept of education surau more emphasis on the authority of a tuanku / sheikh. Surau using a curriculum of book, a fakih (students) cannot ride without first mastering the kitab’s that have been determined. There is no time limit for study at the surau. The ability of students in mastering the kitab’s into the requirement of passing of the surau. Inculcation of adab within a fakih to be the key in the learning process. Surau is Islamic educational institutions in Minangkabau who gave birth to scholar title tuanku. Surau become pioneer founding pesantren Modern in Minangkabau. Sheikh Burhanuddin Ulakan intellectual heritage still exist and survive until today. Keywords : Syeikh Burhanuddin, Surau, Education, Tuanku